PENDAMPINGAN PERAYAAN MAULID NABI MUHAMMAD SAW. SEBAGAI UPAYA PENINGKATAN INTERAKSI SOSIAL MASYARAKAT - Muhammad Yasin; Mustatho Mustatho; Eka Widyanti; Ramdanil Mubarok (LP2M Universitas Ibrahimy, 2023)
The social interactions that have occurred recently have begun to be eroded by individualist and materialist life patterns. Likewise, communication patterns that are increasingly sophisticated with advances in information technology add to the length of the problem of social interaction in society. This community service was carried out to assist in celebrating the birthday of the Prophet Muhammad SAW. to realize an increase in social interaction during the Grand Sangatta housing community, East Kutai Regency, East Kalimantan Province. It was hoped that the birthday Prophet Muhammad SAW implementation could increase togetherness, mutual help, unity and integrity among residents of the Grand Sangatta housing. The method used in this service was the participatory action research method. The service results showed that the social interaction in the middle of the Grand housing community Sangatta was getting more intense. It could be seen from the increasing enthusiasm of the community in participating in activities carried out together as if Khotmil Qur'an at the end of the month, Yasinan and Tahlilan on Friday nights, reading the Al-Waqiah letters every Saturday night, and working together to clean up residential areas. Thus, community service in the form of accompanying the celebration of the Prophet Muhammad's Birthday could positively impact related to social interaction in the Grand Sangatta Housing community.